Escaping to Nature: Ecofeminism in the Children’s Book Bridge to Terabithia - Anandayu Suri Ardini (Program Studi Sastra Inggris Universitas Jenderal Soedirman, 2023)
Similar minor positions between women and nature inspired the emergence of ecofeminism theory, which is suitable for analyzing literary works, including children's literature. This research investigates the issue of how women and nature spiritually empower one another in a children's book entitled Bridge to Terabithia. This paper aims to analyze the harmony of the female figure with the surrounding nature and its impact on gender and class equality. The result of re-reading and analyzing the novel from the perspective of ecofeminism shows that the characters' struggle against social class oppression and gender stereotypes manifested through their escapism to nature. The main female character's courage in rejecting gender stereotypes made the relationship between humans and nature egalitarian. This novel presents nature as the Terabithia Kingdom. The Terabithia Kingdom is where the main characters can escape from all oppressions they experienced in social life.